Mapping Studies on Teachers’ Pedagogical Competence and Its Impact on Learning Quality: A PRISMA Systematic Review - Teresia Antini Senda; Masduki Masduki; Linda Ika Mayasari; Syafa’at Arifil Huda (Journal of Educational Sciences, 2026)
This study aims to map the contribution of teachers’ pedagogical competence to the improvement of learning quality through a SLR based on the PRISMA 2020 protocol. The literature search was conducted using the Google Scholar, Garuda, and Publish or Perish databases within the 2020–2025 period. From an initial 150 publications, a multi-stage screening process based on inclusion and exclusion criteria resulted in 10 articles deemed eligible for analysis. The synthesis results indicate that pedagogical competence consistently serves as a key factor in enhancing learning quality, as reflected in four dominant aspects: understanding students’ characteristics, systematic lesson planning, effective instructional implementation, and continuous evaluation as a basis for improving the learning process. Bibliometric analysis reveals that pedagogical competence occupies the center of a thematic network closely associated with teacher professionalism, learning motivation, digital literacy, and the quality of student outcomes. The findings also show that limited facilities, lack of training, and inconsistency in pedagogical practices remain obstacles in the field. Overall, this review confirms that strengthening pedagogical competence is a fundamental prerequisite for achieving effective and high-quality learning, while also opening opportunities for further research related to teacher professional development models and the integration of technology in pedagogical practices.